2019
DOI: 10.1109/access.2019.2945700
|View full text |Cite
|
Sign up to set email alerts
|

Solar Energy Education Through a Cloud-Based Desktop Virtual Reality System

Abstract: The sustained growth of the solar energy industry has created the need to formalize solar energy education. This paper elucidates a novel, cloud-based, virtual reality (VR) pedagogical system that provides students with the fundamentals of solar or Photovoltaic (PV) cells, solar (PV) modules, and solar (PV) array installation configurations. The VR system was developed using Unity3d software and was integrated with a Learning Management System (LMS). The system was hosted on the Google Cloud Platform. Students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 27 publications
(28 reference statements)
0
13
0
Order By: Relevance
“…We also analyze that the study also can evaluate learning outcomes in the study (Porter et al 2020), student perception (Chamilothori et al 2019;Arias et al 2019;Pirker et al 2018;Abichandani et al 2019;O'Connor et al 2018;Greenwald et al 2018;Makransky et al 2020;Kersting et al 2020;Šiđanin et al 2020), Brain wave activity (Lamb et al 2018), and also can use both learning outcome and student perception Chang et al 2020;Liu et al 2020). Furthermore, we also analyze the trend of virtual reality usage in a broader theme of education and learning using the article record from different keywords after duplicate removed (951 studies).…”
Section: Overall Findingmentioning
confidence: 99%
“…We also analyze that the study also can evaluate learning outcomes in the study (Porter et al 2020), student perception (Chamilothori et al 2019;Arias et al 2019;Pirker et al 2018;Abichandani et al 2019;O'Connor et al 2018;Greenwald et al 2018;Makransky et al 2020;Kersting et al 2020;Šiđanin et al 2020), Brain wave activity (Lamb et al 2018), and also can use both learning outcome and student perception Chang et al 2020;Liu et al 2020). Furthermore, we also analyze the trend of virtual reality usage in a broader theme of education and learning using the article record from different keywords after duplicate removed (951 studies).…”
Section: Overall Findingmentioning
confidence: 99%
“…The proposed frameworks enable multiple laboratories in different geolocations to share and collaborate with respect to learning practices in real time. To improve the learner's engagement, three-dimensional (3D) object models and virtual reality technologies can be used to render an interactive learning environment [13], [14]. In these learning frameworks, teaching objects are presented in 3D scenarios, where learners can adjust the view angles as well as anatomize the objects to view the components they constructed.…”
Section: A Service-experience Awarenessmentioning
confidence: 99%
“…In contrast, the live teacher had the advantage of reducing misunderstandings by answering student concerns, making it more attractive to the students. Abichandani et al performed solar energy education on virtual solar cells, solar modules, and solar arrays using a cloud-based VR education system [27]. Feedback from students indicated that their participation and knowledge acquisition were high.…”
Section: Virtual Reality In Educationmentioning
confidence: 99%